Unravelling the sexual developmental biology of Cystoisospora suis, a model for comparative coccidian parasite studies - Cruz-Bustos, Teresa; Dolezal, Marlies; Feix, Anna Sophia; Ruttkowski, Bärbel; Hummel, Karin; Razzazi-Fazeli, Ebrahim; Joachim, Anja (Frontiers in Cellular and Infection Microbiology, 2023)
The apicomplexan parasite Cystoisospora suis has global significance as an enteropathogen of suckling piglets. Its intricate life cycle entails a transition from an asexual phase to sexual development, ultimately leading to the formation of transmissible oocysts. To advance our understanding of the parasite's cellular development, we complemented previous transcriptome studies by delving into the proteome profiles at five distinct time points of in vitro cultivation through LC/MS-MS analysis. A total of 1324 proteins were identified in the in vitro developmental stages of C. suis, and 1082 proteins were identified as significantly differentially expressed. Data are available via ProteomeXchange with identifier PXD045050. We performed BLAST, GO enrichment, and KEGG pathway analyses on the up-and downregulated proteins to elucidate correlated events in the C. suis life cycle. Our analyses revealed intriguing metabolic patterns in macromolecule metabolism, DNA and RNA-related processes, proteins associated with sexual stages, and those involved in cell invasion, reflecting the adaptation of sexual stages to a nutrient-poor and potentially stressful extracellular environment, with a focus on enzymes involved in metabolism and energy production. These findings have important implications for understanding the developmental biology of C. suis as well as other, related coccidian parasites, such as Eimeria spp. and Toxoplasma gondii. They also support the role of C. suis as a new model for the comparative biology of coccidian tissue cyst stages.